Hipster foods and cafes : framing cohesion and identity - Kartini Aboo Talib @ Khalid; Muhammad Helmy Abd. Gapar; Rahmah Ismail; Suzanna M. Isa (Penerbit Universiti Kebangsaan Malaysia, 2021)
Foods and cafés are experiencing a robust change and have become a trend for consumers. The literal meaning of hipster is anything that goes outside the mainstream culture. Foods and restaurants commonly serve as places to eat, and the serving menu is usually food consumed. On the contrary, hipster cafes and cuisine offer new lists and odd food serving beyond indigeneity foods. This article discusses the hipster foods and restaurants in Bangi, framing new cultural identities to attract consumers. However, the trend attracts youngsters beyond ethnic boundaries but shows a clear-cut class difference. This research is exploratory, and the method applies participant observation and interviews. Thematic analysis is developed based on unstructured interviews with twenty-five respondents to understand the implications of cultural capital and framing towards the state’s reconciliation processes to create a moment of unity amongst multi-ethnic communities. The findings conclude that identity lives in an active form, and foods and dining connect diversity in tranquillity.